Initial report of extraperitoneal pedicle dissection in deep inferior epigastric perforator flap breast reconstruction using the da Vinci SP - Jung, Ji Hyuk; Jeon, Yeo Reum; Lee, Dong Won; Park, Hyung Seok; Lew, Dae Hyun; Roh, Tae Suk; Song, Seung Yong (Archives of plastic surgery, 2022)
The deep inferior epigastric perforator (DIEP) flap has been widely used for autologous breast reconstruction after mastectomy. In the conventional surgical method, a long incision is needed at the anterior fascia of the rectus abdominis muscle to obtain sufficient pedicle length; this may increase the risk of incisional hernia. To shorten the incision, several trials have investigated the use of endoscopic/robotic devices for pedicle harvest; however, making multiple additional incisions for port insertion and operating in the intraperitoneal field were inevitable. Here, we describe the first case, in which a DIEP free flap was successfully made using the da Vinci SP model. Our findings can help surgeons perform operations in smaller fields with a single port in the extraperitoneal space. Moreover, this method is expected to lead to fewer donor-related complications and faster healing.